MOTIVASI SISWA SMA TERHADAP PELAJARAN BAHASA MANDARIN - Erma - Domos (Inovbiz: Jurnal Inovasi Bisnis, 2018)
In the opinion of Indonesian schools, Chinese study has one short coming. This continued for 30 years making many young Indonesians cannot speak Chinese language (Mandarin) and unable to speak dialect too. As society progresses, Chinese once again became Indonesians second language without the auxiliary aid of parents, the teaching of Indonesian literature and language rested on the teacher. Under this special conditions, no one has researched into the Indonesian students method of studying Chinese Language. The author admits personality affect and so does family background, race hence educational level of the language teacher will deeply influence the Indonesian students study of Chinese language. A research of Bandung students in Indonesia shows, diligent study of Chinese language has many reasons. Some students feel that studying Chinese is a kind of challenge, some study because of the encouragement of their parents, while others study out of admiration for China and Chinese culture. Through the study of Chinese language can appreciate Chinese art, culture, history and morality. In addiction, it can help in securing employment. In this research, which is based on a related international study, it referenced previous studies on studying Chinese language as a foreign language  through a questionnaire. Survey focusing on the motivation and analysis factors of Bandung Indonesian student. This research  focused on 5 high schools and a total of 534 students and drew some interesting conclusions. As students study Chinese language, gender, age, grade, origin, length of study, level of parents and teachers have great relevance.